2017
DOI: 10.12788/jhm.2829
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Standardized Costs of Care at Children’s Hospitals

Abstract: BACKGROUND: Though regional variation in healthcare spending has received national attention, it has not been widely studied in pediatrics. OBJECTIVES: (1) To evaluate regional variation in costs of care for 3 inpatient pediatric conditions, (2) assess potential drivers of variation, and (3) estimate cost savings from reducing variation. DESIGN/SETTING/PATIENTS: Retrospective cohort study of hospitalizations for asthma, diabetic ketoacidosis (DKA), and acute gastroenteritis (AGE) at 46 children's hospitals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…16 The conditionspecific variation in cost across hospitals was adjusted for known factors associated with variation in cost, including age, sex, number of CCCs present, material deprivation, and rural vs urban classification to minimize confounding from other factors that may have biased the extent of variation in cost across hospitals. 16,[34][35][36] To alleviate skewness, hospital encounter costs were log transformed before conducting the analysis of variation in cost. The variation in cost per encounter was assessed using 2 methods 16 : intraclass correlation coefficient (ICC) and number of outlier hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The conditionspecific variation in cost across hospitals was adjusted for known factors associated with variation in cost, including age, sex, number of CCCs present, material deprivation, and rural vs urban classification to minimize confounding from other factors that may have biased the extent of variation in cost across hospitals. 16,[34][35][36] To alleviate skewness, hospital encounter costs were log transformed before conducting the analysis of variation in cost. The variation in cost per encounter was assessed using 2 methods 16 : intraclass correlation coefficient (ICC) and number of outlier hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the conditions with the highest cumulative cost because they would either be highly prevalent or highly costly per encounter . The condition-specific variation in cost across hospitals was adjusted for known factors associated with variation in cost, including age, sex, number of CCCs present, material deprivation, and rural vs urban classification to minimize confounding from other factors that may have biased the extent of variation in cost across hospitals …”
Section: Methodsmentioning
confidence: 99%
“…The condition-specific variation in cost across hospitals was adjusted for known drivers of variation in cost to minimize confounding from other factors that may bias the magnitude of variation in cost per encounter across hospitals. 6,[23][24][25] These included age, sex, race/ethnicity, patient type, and number of CCCs present (0, 1, 2, or Ն3). Rural-Urban Commuting Area, primary payer, and income were not included owing to high multicollinearity.…”
Section: Discussionmentioning
confidence: 99%
“…We then determined the variation in cost of hospitalization by condition for the 50 most prevalent and 50 most costly conditions, focusing on their cost per encounter, across hospitals. The condition-specific variation in cost across hospitals was adjusted for known drivers of variation in cost to minimize confounding from other factors that may bias the magnitude of variation in cost per encounter across hospitals . These included age, sex, race/ethnicity, patient type, and number of CCCs present (0, 1, 2, or ≥3).…”
Section: Methodsmentioning
confidence: 99%
“…However, these were costs for all DKA admissions. Costs for children, as with the UK data, were calculated as being lower than those for adults at between $7429 (£5642) and $10 881 (£8264) [20]. Data from Germany did not give estimates of cost per episode, but showed that annual care costs for individuals who had FIGURE 2 A log-normal distribution best fit the imputed total costs ª 2019 Diabetes UK episodes of DKA were increased compared with those who did notcost ratio of 2.2 (95% CI 2.1 to 2.3) for those with just one episode of DKA and 3.6 (95% CI 3.1 to 4.1) for those with more than one episode [16].…”
Section: Discussionmentioning
confidence: 99%